Nuevos medios publicitarios: la influencia del mundo digital en la planificación de medios - Solanas García, Olga; Carreras Margineda, Glòria (Tripodos. Facultat de Comunicació i Relacions Internacionals Blanquerna-URL, 2011)
Technology has changed the rules of the game. The arrival of digital has come to alter the fundamental pillars of marketing. The rapid increase of the digital offer has managed to challenge the conventional, established (analog) media, and in particular television, print media and exterior media. The eruption of the digital media is a milestone, and never before had a medium reached so many people in such a short time. In this paper we analyze technological development in the field of the internet and digital television in Spain. Then, we identify the primary consequences for media consumption, the reaction of advertisers, and the process of adaptation led by the media themselves, especially in the area of commercialization. Finally, we confront the role of media agencies, faced with this new panorama of drastic changes. KEY WORDS: (new) advertising media, media planning, digital planning, digital media, media audience, internet advertising, digital television, TDT, media consumption, media agencies, digital technology, communication media, digital environment, media panorama, media efficiency, liquid content, on-off media, interactivity, television scenario, advertising investment, advertising activity, future of the media, media trends.Olga Solanas García es licenciada en Comunicación y Relaciones Públicas por la Universitat Autònoma deBarcelona (UAB). Actualmente es directora de servicios al cliente de MEC Barcelona. Glòria Carreras Margineda es diplomada en Ciencias Económicas y Empresariales por la Universidad de Barcelona y máster en Dirección de Marketing por EADA. Actualmente es directora de MEC Barcelona.Ambas son profesoras colaboradoras del Postgrado dePlanificación Estratégica de la Comunicación Empresarial (PECE) en la Facultat de Comunicació Blanquerna (URL) y coordinadoras y profesoras colaboradoras de la asignatura de Análisis de Audiencias y su Impacto en el Diseño de las Estrategias de Comunicación.PALABRAS CLAVE: (nuevos) medios publicitarios, planificación de medios, planificación digital, medios digitales, audiencia de medios, publicidad en internet, televisión digital, TDT, consumo de medios, agencias de medios, tecnología digital, medios de comunicación, entorno digital, panorama de medios, eficacia en medios, contenido líquido, medios on-off, interactividad, escenario televisivo, inversión publicitaria, actividad publicitaria, futuro de los medios, tendencias de los medios.